Strategies for Alleviating Electrode Expansion of Graphite Electrodes in Sodium‐Ion Batteries Followed by In Situ Electrochemical Dilatometry. Issue 3 (19th November 2020) - Escher, Ines; Kravets, Yuliia; Ferrero, Guillermo A.; Goktas, Mustafa; Adelhelm, Philipp
Abstract : The electrochemical intercalation/deintercalation of solvated sodium ions into graphite is a highly reversible process, but leads to large, undesired electrode expansion/shrinkage ("breathing"). Herein, two strategies to mitigate the electrode expansion are studied. Starting with the standard configuration (−) sodium | diglyme (2G) electrolyte | graphite (poly(vinylidene difluoride) (PVDF) binder) (+), the PVDF binder is first replaced with a binder made of the sodium salt of carboxymethyl cellulose (CMC). Second, ethylenediamine (EN) is added to the electrolyte solution as a co‐solvent. The electrode breathing is followed in situ (operando) through electrochemical dilatometry (ECD). It is found that replacing PVDF with CMC is only effective in reducing the electrode expansion during initial sodiation. During cycling, the electrode breathing for both binders is comparable. Much more effective is the addition of EN. The addition of 10 v/v EN to the diglyme electrolyte strongly reduces the electrode expansion during the initial sodiation (+100% with EN versus +175% without EN) as well as the breathing during cycling. A more detailed analysis of the ECD signals reveals that solvent co‐intercalation temporarily leads to pillaring of the graphite lattice and that the addition of EN to 2G leads to a change in the sodium storage mechanism. Abstract : The electrode expansion and shrinkage ("breathing") of a graphite electrode in a sodium‐ion battery is investigated. Changing the binder material from poly(vinylidene difluoride) to the sodium salt of carboxymethyl cellulose results in a smaller electrode breathing in the first cycle but does not influence the following cycles. The addition of ethylenediamine as co‐solvent results in reduced breathing in all cycles.